Should we ventilate differently in an adaptable context? An exploratory LCA-study - Seuntjens, Oskar; Belmans, Bert; Buyle, Matthias; Kabbara, Zakarya; Jorens, Sandy; Audenaert , Amaryllis (CLIMA 2022 conference, 2022)
Currently a great number of buildings, that are not able to meet the evolving needs of building owners and users, are being demolished before reaching their technical life span. To avoid such waste, it is crucial that buildings have an adaptable design in order to allow for flexible building usage. Ventilation is crucial in this transition as a flexible building usage can lead to fluctuating ventilation requirements. However, knowledge about how to choose between ventilation systems in an adaptable context is sorely lacking. In this research, an exploratory LCA-study will be carried out on two ventilation systems in an adaptable context over a period of 15 years. The case study concerns a school building where a reconfiguration of the floorplan design is planned every five years. The first ventilation system concerns a centralized balanced mechanical ventilation system which uses a heat recovery system and ductwork to distribute the air to all the classrooms. The second ventilation system is a ductless exhaust ventilation system which uses three exhaust fans to extract air and vents above windows to supply air naturally. Despite the centralized balanced ventilation system having a higher energy efficiency, the environmental impact of this ventilation system is 40% higher than the impact of the ductless exhaust ventilation system. This is caused by the use of a great amount of ductwork and an air handling unit. The largest share of the environmental impact of the ductless exhaust ventilation system is related to the additional energy that is needed to condition the temperature in the classrooms. Further research should include other ventilation systems and flexibility scenarios as well. Moreover, follow-up research should not only quantify the environmental impact but also assess the financial impact of ventilation systems in an adaptable context.